Contactless real-time heart rate predicts the performance of elite athletes: evidence from Tokyo 2020 Olympic archery competition - Lu, Y.; Zhong, S. (Psychological Science, 2023)
It is widely recognized that psychological stress impairs performance for elite athletes, yet direct evidence is scarce when it comes to high-stakes competition because measuring real-time psychological stress without interference is often challenging. Contactless real-time heart rate—a technology-enabled biomarker of stress—was measured and broadcast on TV during the 2020 Tokyo Olympics archery competition for the first time in sports. Here we examined whether the real-time heart rate of 122 adult archers predicted their performance in this unique setting. We found that higher heart rate—which indicates an increase in psychological stress—is associated with lower scores, correlation coefficient r(2096) = -.076, p < .001, and the observation is robust after we controlled for fixed effects at the individual and match level. Our results provide the first direct evidence in support of the detrimental effect of psychological stress measured by a real-time biomarker in a high-stakes competitive setting.